ANALISIS DAN DESAIN SISTEM PENDATAAN KEWIRAUSAHAAN MAHASISWA - Budhiraja, Irsyad; Febbyanti, Adellyna Cantica; Zahroh, Syifaul Aini; Purnomo, Marcello Hamasias Dwi Greatajoy; Safitri, Anita (Journal of Digital Business and Innovation Management, 2023)
The student entrepreneurship data application is an innovative solution to enhance entrepreneurship's efficiency and development within the higher education environment. In an increasingly competitive era, entrepreneurship has become crucial in harnessing students' potential to create job opportunities and drive economic growth. This application is designed to facilitate collecting, processing and analysing data related to student entrepreneurship across various universities. Integrated and systematic data management will assist educational institutions in monitoring the progress of student entrepreneurship, identifying trends and patterns, and taking strategic measures to support entrepreneurial activities. Key features of this application include student entrepreneurship registration, collection of individual and business profile data, document archiving, and the generation of entrepreneurship reports and analysis. Students can register themselves as entrepreneurs and provide information about their ongoing or past business ventures. Faculty, counsellors, and other relevant parties can then utilise this data to provide appropriate guidance, training, and support. Furthermore, the application provides various data analysis and visualization tools, aiding in identifying untapped business trends and opportunities. Information regarding business types, success rates, and challenges student entrepreneurs face will provide valuable insights to universities in developing curricula, programs, and entrepreneurship development activities. With the student entrepreneurship data application, it is expected that educational institutions can optimize their role in supporting student entrepreneurship. The information collected through this application can be utilized to track progress, identify new needs and opportunities, and design appropriate strategies to enhance students' success in their entrepreneurial endeavours.